Semi-Supervised EEG Signals Classification System for Epileptic Seizure Detection - Abdelhameed, Ahmed M.; Bayoumi, Magdy (IEEE signal processing letters, 2019)
In the past few decades, measuring and recording the brain electrical activities using Electroencephalogram (EEG) has become a standout amongst the tools utilized for neurological disorders' diagnosis, especially seizure detection. In this letter, a novel epileptic seizure detection system based on classifying raw EEG signals' recordings, eliminating the overhead of engineered feature extraction, is proposed. The system employs a mixing of unsupervised and supervised deep learning utilizing a one-dimensional convolutional variational autoencoder. To ascertain the robustness of the system against classifying unseen data, the evaluation of the proposed system is done using k-fold cross-validation. The classification results between normal and ictal cases have achieved a 100% accuracy while the classification results between the normal, inter-ictal and ictal cases accomplished a 99% overall accuracy which makes our system one of the most efficient among other state-of-the-art systems.